Analisis Framing Zhongdan Pan & Gerald M Kosicki Terhadap Pemberitaan Jawaban Anies Baswedan Terkait Permasalahan Polusi Udara di Jakarta Dalam Debat Pertama Calon Presiden 2024 - Khairunnisa Putri, Ghaza; Mahar Rizqi, Fikriana (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Slamet Riyadi Surakarta, 2024)
The issue of Jakarta's air pollution, highlighted in the 2024 Presidential Debate, has sparked both support and criticism in the public sphere, with various parties presenting opinions and critiques regarding the proposed solutions. As a social watchdog, the media is expected to be neutral. However, political affiliations and other interests often cause media to deviate from the principle of objectivity, thereby influencing public perception. This study aims to compare the framing strategies of Tvonenews.com and Metrotvnews.com in covering Anies Baswedan's responses to the air pollution issues in Jakarta during the First Presidential Debate of 2024. The research employs a qualitative method and the framing approach of Zhongdang Pan and Gerald M. Kosicki. The findings reveal that Tvonenews.com emphasizes Anies's sharp responses to criticisms from Prabowo Subianto, whereas Metrotvnews.com focuses on presenting policy explanations but does not delve deeply into the effectiveness of the policies or the broader context.